Notch Signaling Controls Transdifferentiation of Pulmonary Neuroendocrine Cells in Response to Lung Injury. (1st December 2017) - Yao, Erica; Lin, Chuwen; Wu, Qingzhe; Zhang, Kuan; Song, Hai; Chuang, Pao‐Tien
Abstract: Production of an appropriate number of distinct cell types in precise locations during embryonic development is critical for proper tissue function. Homeostatic renewal or repair of damaged tissues in adults also requires cell expansion and transdifferentiation to replenish lost cells. However, the responses of diverse cell types to tissue injury are not fully elucidated. Moreover, the molecular mechanisms underlying transdifferentiation remain poorly understood. This knowledge is essential for harnessing the regenerative potential of individual cell types. This study investigated the fate of pulmonary neuroendocrine cells (PNECs) following lung damage to understand their plasticity and potential. PNECs are proposed to carry out diverse physiological functions in the lung and can also be the cells of origin of human small cell lung cancer. We found that Notch signaling is activated in proliferating PNECs in response to epithelial injury. Forced induction of high levels of Notch signaling in PNECs in conjunction with lung injury results in extensive proliferation and transdifferentiation of PNECs toward the fate of club cells, ciliated cells and goblet cells. Conversely, inactivating Notch signaling in PNECs abolishes their ability to switch cell fate following lung insult. We also established a connection between PNEC transdifferentiation and epigenetic modification mediated by the polycomb repressive complex 2 and inflammatory responses that involve the IL6‐STAT3 pathway. These studies not only reveal a major pathway that controls PNEC fate change following lung injury but also provide tools to uncover the molecular basis of cell proliferation and fate determination in response to lung injury. Stem Cells 2018;36:377–391 Abstract : Schematic diagram of transdifferentiation of pulmonary neuroendocrine cells (PNECs) that highlights the role of lung injury and Notch signaling in inducing cell proliferation and fate change toward club cells and ciliated cells. This process also involves epigenetic modification and inflammatory responses that interact with Notch signaling and injury responses. This model provides a new framework to uncover the molecular mechanisms of PNEC transdifferentiation.